PENYULUHAN KESEHATAN PADA CAREGIVER LANSIA MENGENAI POLA HIDUP SEHAT BAGI LANSIA - Lilyana, M.T.A.; Cempaka, A.A. (Buletin Udayana Mengabdi; Vol 22 No 3 (2023): Buletin Udayana MengabdiDO - 10.24843/BUM.2023.v22.i03.p09, 2023)
Aging is a natural process that will be experienced by everyone, but age must still have good qualities. A good quality of life for the elderly can be achieved by physical activity such as exercise and good nutrition. The aim of this activity is socialization to increase knowledge for 13 elderly caregivers about: the elderly, the importance of physical activity for the elderly, nutritional needs for the elderly, assessment of basic health status in the form of measuring height and weight. Activities carried out in the form of lectures and demonstrations. Evaluation of the level of knowledge based on the results of pre-test and post-test questionnaires about physical activity and nutritional intake needs of the elderly, obtained by participants who have a good level of knowledge increased to 92%. So it can be concluded that the activities that have been carried out have an influence on increasing nutritional knowledge of caregivers. Keywords: Caregiver, elderly, healthy lifestyle, physical activity, nutrition